Flame-retardant solid electrolyte as well as preparation method and application thereof
By using a cage-type three-dimensional network structure composition in solid electrolytes, combining lithium salts and organic phosphorus-based flame retardants, the problems of safety hazards and performance of traditional lithium batteries are solved, and a balance between high mechanical and electrochemical properties is achieved. Improves the safety and energy density of lithium batteries.
Patent Information
- Application Number
- CN202411522418.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-14
AI Technical Summary
Traditional liquid electrolyte lithium batteries have safety hazards such as thermal runaway and leakage. Solid electrolytes have trade-offs in taking into account both electrochemical performance and flame retardant performance, making it difficult to find a balance between high performance and safety.
Using a first polymer monomer with a cage polysilsesquioxane structure and a second polymer monomer with an ethylene glycol dimethacrylate structure, combining lithium salts, organic phosphorus-based flame retardants, polymerization reaction initiators and Organic solvents form cage-shaped three-dimensional network structures through in-situ polymerization, improve mechanical and electrochemical properties, and build fast lithium ion channels through uniform dispersion of lithium salts and organic components.
The high mechanical and electrochemical properties of solid electrolytes are achieved, the ion transport efficiency and flame retardancy of the electrolyte are improved, and the cycle stability and safety performance of lithium metal batteries are ensured.
Smart Images

Figure CN119315101A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state lithium batteries, and in particular relates to a flame-retardant solid-state electrolyte and a preparation method and application thereof. Background Art
[0002] With the rapid economic growth and continuous technological advancement, human society's demand for energy is growing. In this context, high-performance and safe energy storage devices have become the focus of research. As an important energy storage device, lithium batteries have been widely used in various fields such as electric vehicles, communication tools, aerospace, etc. However, traditional liquid electrolyte lithium batteries have safety hazards such as thermal runaway and leakage, which seriously threaten people's lives and property. Solid electrolytes have become a research hotspot in the battery field due to their high safety and environmental friendliness.
[0003] Among solid electrolytes, polymer electrolytes have attracted widespread attention due to their good flexibility, easy processing into various shapes, and low cost. Polymer electrolytes are mainly composed of polymer matrix and lithium salt, and realize the charging and discharging process of the battery through ion transport. However, the flammability and electrochemical properties of polymer electrolytes are not compatible, which limits their application in the field of high-performance and safe batteries. Therefore, the development of high-performance flame-retardant solid polymer electrolytes has become an important direction of current research.
[0004] In the solid electrolyte system, the method of encapsulating polymers with organic electrolytes is adopted. Compared with the traditional small molecule organic electrolytes, polymers show lower combustion tendency and better mechanical properties. Specifically, with the increase of polymer proportion or its molecular weight, the flame retardant properties of solid electrolytes are significantly enhanced, and its mechanical strength is also improved accordingly. However, in terms of ion transfer rate, small molecule electrolytes show better electrochemical properties due to their higher ion diffusion rate than ion transfer achieved by chain segment movement in polymers. Therefore, in the design of solid electrolytes, there is a certain trade-off between electrochemical performance and flame retardant performance. Similarly, the improvement of electrochemical performance is often in conflict with the enhancement of mechanical properties. In the study of flame-retardant solid polymer electrolytes, researchers mainly achieve flame retardancy of polymers in the following two ways: one is to improve the rigidity of molecular segments so that polymers are not easy to decompose at high temperatures; the other is to form a tight polymer network, improve thermodynamic stability and reduce flammability. However, the above methods are often at the expense of the electrochemical properties of the electrolyte. Therefore, the researchers hope to improve the ion transfer efficiency and optimize the electrochemical performance by adjusting the polymer molecular structure, introducing functional groups, etc. on the basis of ensuring flame retardant properties. This ensures that when developing flame retardant solid polymer electrolytes, both mechanical and electrochemical properties can be taken into account, ensuring that the battery has high safety while also having high energy density and service life. Summary of the invention
[0005] In view of the deficiencies of the prior art, the present invention provides a flame-retardant solid electrolyte and a preparation method and application thereof. The flame-retardant solid electrolyte has a strong liquid retention effect and good flame retardancy, and can take into account the electrochemical properties and mechanical properties of the electrolyte, and exhibits high cycle stability in lithium metal batteries, which is of great significance to the development of safe and high-performance solid-state batteries.
[0006] In a first aspect, the present invention provides a composition for preparing a flame retardant solid electrolyte, comprising: a) a first polymerizable monomer as shown in formula (I); b) a second polymerizable monomer as shown in formula (II); c) a lithium salt; d) an organic phosphorus flame retardant; e) a polymerization initiator; and f) an organic solvent;
[0007]
[0008] Among them, R is a C1-C6 alkene group, preferably a C1-C3 alkene group; n is an integer of 4 to 132, preferably an integer of 10-60, and more preferably an integer of 20-40.
[0009] As shown in formula (I), the cage structure of the first polymerized monomer has eight reactive sites, which can be evenly distributed in the electrolyte as crosslinking points. The internal silicon-oxygen bonds and the long molecular chains formed after external crosslinking constitute an organic-inorganic hybrid structure, which can improve the mechanical properties and reduce the flammability of the electrolyte. Within the value range of n in formula (II), the crosslinking density can be flexibly controlled.
[0010] In some embodiments, the molar ratio of the first polymerized monomer to the second polymerized monomer is 0.0625 to 0.25. By limiting the molar ratio of the reactive monomers, the molecular structure of the cage-type framework is controlled.
[0011] In some embodiments, the lithium salt is at least one of lithium hexafluoroarsenate (LiAsF6), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(difluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium hexafluorophosphate (LiPF6), and lithium tetrafluoroborate (LiBF4); the mole fraction of the lithium salt in the composition is 0.5 to 2.5 M, and within the specified mole fraction range, the rate stability of the electrolyte is good.
[0012] In some embodiments, the organophosphorus flame retardant is at least one of phosphazene, tributyl phosphate (TBP), triphenyl phosphate (TPP), ammonium polyphosphate (APP), dimethyl methyl phosphate (DMMP), and triphenyl phosphite; the mass of the organophosphorus flame retardant is 0.5 to 5% of the total mass of the organic solvent.
[0013] In some embodiments, the polymerization initiator is an azo initiator, and the mass of the polymerization initiator is 0.01 to 0.05% of the total mass of the monomers;
[0014] In some embodiments, the organic solvent is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethylene glycol dimethyl ether, and ethyl methyl carbonate, and the mass of the organic solvent is 5-20% of the total mass of the composition. By adding a small amount of liquid organic components, the electrochemical properties of the electrolyte, such as ion conductivity and ion migration number, are improved, and a small amount of organic components are uniformly retained in the polymer cage framework to balance the mechanical properties and electrochemical properties of the electrolyte.
[0015] In a second aspect, the present invention provides a method for in-situ preparation of a flame retardant solid electrolyte, comprising: polymerizing the aforementioned composition in-situ at a temperature of 40 to 80° C. for 2 to 10 hours to form a flame retardant solid electrolyte.
[0016] In a third aspect, the present invention provides a flame retardant solid electrolyte prepared according to the aforementioned method.
[0017] In a fourth aspect, the present invention provides a solid-state lithium battery comprising the aforementioned composition or flame-retardant solid electrolyte.
[0018] In a fifth aspect, the present invention provides an electric device comprising the aforementioned solid-state lithium battery.
[0019] The beneficial effects of the present invention are:
[0020] 1. The composition for preparing a flame-retardant solid electrolyte provided by the present invention particularly adopts a first monomer having a cage-shaped polysilsesquioxane structure and a second monomer having an ethylene glycol dimethacrylate structure as polymerization monomers, and is compounded with a lithium salt as an active substance, a functional auxiliary organic phosphorus flame retardant, a polymerization initiator and an organic solvent, and can be polymerized in situ to form a solid electrolyte with a cage-shaped three-dimensional network as a skeleton, and lithium salt and other organic components (organic phosphorus flame retardant and organic solvent) are uniformly dispersed in the skeleton, which has the following advantages:
[0021] 1) The skeleton structure is stable, which greatly improves the mechanical properties of the solid electrolyte. At the same time, the electrolyte components including organic solvents, lithium salts, and flame retardants surrounding the network can construct fast lithium ion channels, and the cage-type three-dimensional network structure can capture anions in the lithium salt, realize single ion transport of the electrolyte, increase the number of electrolyte lithium ion migration, and improve the ion transport efficiency of the electrolyte. It shows good cycle rate performance in lithium metal batteries. Therefore, the present invention balances the incompatibility between the electrochemical properties and mechanical properties of the solid electrolyte, so that the electrolyte has both high ionic conductivity and good mechanical properties, which can ensure stable operation of the battery.
[0022] 2) The inorganic nanophase composed of silicon-oxygen bonds inside the skeleton and the organic phase outside the cage enhance the chemical stability of the electrolyte, making it non-flammable, and the cage-type polysilsesquioxane can capture free radicals during the combustion process and block combustion. Therefore, the skeleton improves the flame retardancy of the solid electrolyte and greatly improves the safety performance of the electrolyte.
[0023] 2. The method for preparing the flame-retardant solid electrolyte provided by the present invention can obtain the final flame-retardant solid electrolyte by heating to decompose the polymerization initiator and initiate in-situ polymerization of the monomer. The preparation method is a safe, practical and simple preparation method with low reaction conditions and equipment requirements, and is easy to realize industrialization.
[0024] 3. The flame-retardant solid electrolyte provided by the present invention can be used to prepare solid-state lithium batteries and further applied to various electric devices, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of the molecular structure of the flame-retardant solid electrolyte of the present invention;
[0026] Figure 2 It is the carbon-1NMR spectra of POSS in Example 1;
[0027] Figure 3 is the carbon-1NMR spectrum of PEGDMA in Example 1;
[0028] Figure 4 is the carbon nuclear magnetic resonance spectrum of the flame-retardant solid electrolyte in Example 1;
[0029] Figure 5 is the hydrogen nuclear magnetic resonance spectrum of POSS in Example 1;
[0030] Figure 6 is the hydrogen nuclear magnetic resonance spectrum of PEGDMA in Example 1;
[0031] Figure 7 is a hydrogen nuclear magnetic resonance spectrum of the flame-retardant solid electrolyte in Example 1;
[0032] Figure 8 is an infrared spectrum of the flame-retardant solid electrolyte in Example 1;
[0033] Fig. 9 is the electrochemical impedance spectrum of the assembled symmetrical battery in Example 1;
[0034] Fig.10 is the electrochemical impedance spectrum of the assembled symmetrical battery in Example 2;
[0035] Fig.11 is the electrochemical impedance spectrum of the assembled symmetrical battery of Example 3;
[0036] Fig.12 The flame retardant solid electrolyte of Example 1 of the present invention is compared with the combustion test results of the commercial electrolyte LB-008, wherein A: commercial electrolyte LB-008; B: flame retardant solid electrolyte of the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] The molecular structure diagram of the flame-retardant solid electrolyte prepared in the embodiment of the present invention is as follows Figure 1 As shown, the carbon nuclear magnetic resonance spectra of POSS, PEGDMA and flame-retardant solid electrolyte in Example 1 are respectively as shown in Figure 2 , Figure 3 , Figure 4 As shown, the H NMR spectra are Figure 5 , Figure 6 , Figure 7 As shown, the infrared spectrum of the flame-retardant solid electrolyte is as follows Figure 8 shown.
[0039] Example 1
[0040] Weigh 0.633 g of cage-type octavinyl-polysilsesquioxane (octavinyl POSS), 5.28 g of polyethylene glycol dimethacrylate (PEGDMA, ethylene glycol polymerization degree n=4) and 6 mg of azobisisobutyronitrile, mix well, add 0.6 g of ethylene carbonate: ethyl methyl carbonate = 3:7 organic solvent, 30 mg of phosphazene, 1.5 M of lithium bistrifluoromethylsulfonyl imide and 0.5 M of lithium hexafluorophosphate, mix well to obtain a polymer precursor; heat the polymer precursor at 40°C for 10 h to obtain a flame retardant solid electrolyte.
[0041] The prepared flame-retardant solid electrolyte was used to assemble a symmetrical battery and an impedance test was performed. The test results are as follows: Fig. 9 As shown in the figure, the impedance of the flame-retardant solid electrolyte is 246.7 ohms. Combined with the thickness of the flame-retardant solid electrolyte of 0.1 cm, the effective contact area is 2.01 cm 2 , according to the formula It is calculated that the ionic conductivity of the electrolyte is σ = 2.01 × 10 -4 S cm -1 .
[0042] The prepared flame-retardant solid electrolyte and commercial electrolyte LB-008 (1 mol LiPF6EC: DEC1:1) were used in combustion experiments. The results are as follows Fig.12 It can be seen that compared with the commercial electrolyte LB-008, the solid electrolyte of the present invention effectively inhibits the spread of flames and extinguishes the flames after burning for about 6 seconds, indicating that the solid electrolyte of the present invention has excellent flame retardant properties and can improve the safety of solid-state batteries.
[0043] Example 2
[0044] Weigh 0.633 g of cage-type octavinyl-polysilsesquioxane (octavinyl POSS), 6 g of polyethylene glycol dimethacrylate (ethylene glycol polymerization degree n=13) and 7 mg of azobisisobutyronitrile, mix well, add 0.67 g of an organic solvent of ethylene carbonate:ethyl methyl carbonate=3:7, 35 mg of phosphazene, 1.5 M of lithium bistrifluoromethylsulfonyl imide and 0.5 M of lithium hexafluorophosphate, mix well to obtain a polymer precursor; heat the polymer precursor at 40°C for 10 h to obtain a flame-retardant solid electrolyte.
[0045] The prepared flame-retardant solid electrolyte was used to assemble a symmetrical battery and an impedance test was performed. The test results are as follows: Fig.10 As shown in the figure, the impedance of the flame-retardant solid electrolyte is 119.7 ohm. Combined with the thickness of the flame-retardant solid electrolyte of 0.1 cm, the effective contact area is 2.01 cm 2 , according to the formula The calculated ionic conductivity of the electrolyte is σ = 4.16 × 10 -4 Scm -1 .
[0046] Example 3
[0047] Weigh 0.633 g of cage-type octavinyl-polysilsesquioxane (octavinyl POSS), 8 g of polyethylene glycol dimethacrylate (ethylene glycol polymerization degree n=42) and 9 mg of azobisisobutyronitrile, mix well, add 0.9 g of ethylene carbonate: ethyl methyl carbonate = 3:7 organic solvent, 45 mg of phosphazene, 1.5 M of lithium bistrifluoromethylsulfonyl imide and 0.5 M of lithium hexafluorophosphate, mix well to obtain a polymer precursor; heat the polymer precursor at 40°C for 10 h to obtain a flame-retardant solid electrolyte.
[0048] The prepared flame-retardant solid electrolyte was used to assemble a symmetrical battery and an impedance test was performed. The test results are as follows: Fig.11 As shown in the figure, the impedance of the flame-retardant solid electrolyte is 168.4 ohm. Combined with the thickness of the flame-retardant solid electrolyte of 0.1 cm, the effective contact area is 2.01 cm2 , according to the formula The calculated ionic conductivity of the electrolyte is σ = 3.0 × 10 -4 Scm -1 .
[0049] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A composition for preparing a flame retardant solid electrolyte, characterized in that: The composition comprises: a) a first polymerizable monomer as represented by formula (I); b) a second polymerizable monomer as represented by formula (II); c) lithium salts; d) Organic phosphorus flame retardants; e) a polymerization initiator; and f) organic solvents; Wherein, R is a C1-C6 alkene group; and n is an integer from 4 to 132.
2. The composition according to claim 1, characterized in that The R is a C1-C3 alkene group, and n is an integer of 10 to 60.
3. The composition according to claim 1, characterized in that The molar ratio of the first polymerizable monomer to the second polymerizable monomer is 0.0625 to 0.
25.
4. The composition according to claim 1, characterized in that The lithium salt is at least one of lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium hexafluorophosphate, and lithium tetrafluoroborate; and the molar fraction of the lithium salt in the composition is 0.5 to 2.5M.
5. The composition according to claim 1, characterized in that The organophosphorus flame retardant is at least one of phosphazene, tributyl phosphate, triphenyl phosphate, ammonium polyphosphate, dimethyl methyl phosphate and triphenyl phosphite; the mass of the organophosphorus flame retardant is 0.5-5% of the total mass of the organic solvent.
6. The composition according to claim 1, characterized in that The polymerization initiator is an azo initiator, and the mass of the polymerization initiator is 0.01 to 0.05% of the total mass of the monomer; And / or, the organic solvent is at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethylene glycol dimethyl ether, and ethyl methyl carbonate, and the mass of the organic solvent is 5-20% of the total mass of the composition.
7. A method for in-situ preparation of a flame-retardant solid electrolyte, characterized in that: The method comprises: subjecting the composition according to any one of claims 1 to 6 to in-situ polymerization at a temperature of 40 to 80° C. for 2 to 10 hours to form a flame-retardant solid electrolyte.
8. The flame-retardant solid electrolyte prepared according to the method of claim 7.
9. A solid-state lithium battery, characterized in that: The solid-state lithium battery comprises the composition according to any one of claims 1 to 6 or the flame-retardant solid electrolyte according to claim 8.
10. An electric device, characterized in that: The electric device comprises the solid-state lithium battery according to claim 9.
Citation Information
Cited By
Non-aqueous electrolyte solution and lithium secondary battery
CN120033324A
Flame-retardant gel electrolyte, preparation method thereof and lithium ion battery
CN121507080A
A flame-retardant gel electrolyte, its preparation method, and a lithium-ion battery
CN121507080B